Comparative Accuracy of Cone-Beam Computed Tomography and Clearing Technique in Studying Root Canal and Apical Morphology of Mandibular Canines - Naseri, Mandana; Ahangari, Zohreh; Bagheri, Nastaran; Jabbari, Sanaa; Gohari, Atefeh (Iranian Endodontic Journal, 2019)
Introduction: Knowledge about root canal anatomy improves the long-term prognosis of endodontic treatment. This study aimed to investigate the accuracy of cone-beam computed tomography (CBCT) in assessment of morphology of root canal and apex in mandibular canines compared with the clearing technique. Methods and Material: In this in vitro study, 33 extracted mandibular canines were subjected to CBCT with 0.1 mm voxel size. Number and type of canals, prevalence of accessory canals, anastomosis, apical delta and distance from apical constriction (AC) to apical foramen (AF) and to anatomic apex (AA) and also distance from AF to the AA were determined on CBCT scans. After access cavity preparation, a #8 K file was passed through the main apical foramen. Its direction and distance from anatomic apex was determined under a stereomicroscope. After clearing and staining of teeth, other criteria were determined with stereomicroscope under 16× magnification and served for comparison with CBCT data. The agreement of two methods were evaluated by intra-class correlation and kappa coefficients for quantitative and qualitative data, respectively. Results: Most (93.9%) canine teeth were Vertucci’s type I, followed by type III configuration in both CBCT and clearing techniques. The results of both techniques were not in agreement for assessment of accessory canals, however acceptable agreement was noted between them for detection of apical delta and also assessment of apical foramen deviation in buccolingual and mesiodistal directions. Both of two techniques had excellent agreement for evaluating the distances from AF to AA, AC to AF and AC to AA. Conclusions: CBCT is a reliable tool in assessment of root canal and apical topography in mandibular canines, however its use in accessory canal detection is not recommended. Keywords: Canine Tooth; Clearing Technique; Cone-Beam Computed Tomography; Tooth Apex